Halogen···Halogen interactions in host - guest systems - Amombo Noa, Francoise Mystere (Department of Chemistry, 2018)
For a few decades now, halogen bonds which are non-covalent interactions, have gained a lot of interest in the science community due to their applications in diverse research areas. Halogen bonding (XB) is an interaction that occurs between electron deficient halogen compounds and electron donors. This is an established non-covalent interaction in the solid and gaseous phase. In this thesis, the work presented deals with the investigation of halogen bond interactions in host-guest complexes utilising both experimental and theoretical techniques. Two host compounds, tetrakis-4-(bromophenyl)ethylene and its iodo-analogue were synthesised for the studies reported in Chapter 3, 4 and 5. Chapter 3, deals with the classification of halogen···halogen interactions using halogenated methanes as guest solvents. Here, the inclusion complexes can be classified into different types of halogen bonds depending on their geometry. Type I, which are of van der Waals in nature usually have X···X distances greater than the sum of their van der Waals radii. Type IIa and IIb are interactions which are considered to be attractive and their X···X distances are usually shorter than those of type I. The compounds obtained in Chapter 3 were used to study both the kinetics of desolvation and the kinetics of enclathration for the solid host-methyl iodide vapour reactions, to obtain their rate law and determine activation energies. In Chapter 4, the two hosts mentioned above were utilised to form inclusion compounds with a series of halogenated compounds for guest exchange reactions. The structures of the starting inclusion compounds were exposed to the vapours of the second incoming guests to form intermediate complexes and final compounds, which were used to analyse the halogen···halogen interactions in their structures. NMR spectroscopy was performed on selected crystals to monitor the guest exchange experiment and the rate law of each exchange reaction was established. Tetrakis-4-(bromophenyl)ethylene and its iodo-analogue were also used as host compounds in Chapter 5. Here, halogen···halogen interactions are also classified and two novel polymorphs of tetrakis-4-(iodophenyl)ethylene with 3-picoline (3PIC) are reported. Kinetics of enclathration by suspension was conducted on two of the bromohost inclusion compounds (with 3-bromopyridine and 3-picoline) at 25 °C and 35 °C. Competition between hydrogen and halogen bonding was performed in Chapter 6, using three similar but subtly different host compounds with halogenated substituted pyridines as guests. IR spectroscopy and Hirshfeld surface analysis were utilised for further characterisation of these inclusion compounds. The synthesis of halogenated Werner clathrates containing Cl-, Br- and I- in Chapter 7, was conducted with various guests of substituted pyridines. Compounds, which were derived from NiI₂ yielded ionic complexes, forming iodide anions. Iodine was added to these complexes to form tri-iodide anions. The Werner clathrates obtained with the 4-picoline (4PIC) could also be directly synthesised by the exposure of NiCl₂/NiBr₂ to the vapour of 4PIC. Kinetics of enclathration of these two solid-vapour reaction compounds were also analysed. All the structures in this study were elucidated using single crystal X-ray diffraction. Thermal analyses such as thermogravimetry (TG), hot stage microscopy (HSM) and differential scanning calorimetry (DSC) were used for the determination of the thermal behaviour of the new compounds. Variable temperature powder X-ray diffraction was also carried out for the characterisation of the new compounds.